The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/coatings11101147
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Efficiency Flame-Retardant and Superhydrophobic Cotton Fabric by a Multi-Step Dipping

Abstract: Cotton fabric, as an important material, is suffering from some defects such as flammability, easy pollution and so on; therefore, it is important to make a flame-retardant and superhydrophobic modification on cotton fabric. In this study, we demonstrated a preparation of high-efficiency flame-retardant and superhydrophobic cotton fabric with double coated construction by a simple multi-step dipping. First, the fabric was immersed in branched poly(ethylenimine) (BPEI) and ammonium polyphosphate (APP) water dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Therefore, the TG curve was similar to the CS/CNF one, but showed the lowest temperature (255 °C) of the fastest decomposition rate due to the thermal decomposition of APP and BPEI. After 600 °C, the CS/CNF and CS/CNF/APP/BPEI composite films had higher residual mass (28% and 26.1%, respectively) than that of the pure one, suggesting the addition of CNF, APP and BPEI was beneficial to the thermal stability of the CS-based composite film [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the TG curve was similar to the CS/CNF one, but showed the lowest temperature (255 °C) of the fastest decomposition rate due to the thermal decomposition of APP and BPEI. After 600 °C, the CS/CNF and CS/CNF/APP/BPEI composite films had higher residual mass (28% and 26.1%, respectively) than that of the pure one, suggesting the addition of CNF, APP and BPEI was beneficial to the thermal stability of the CS-based composite film [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analogously, BPEI, APP and fluorodecyl polyhedral polysiloxane were deposited on the surface of the cotton fabric by simple layer-by-layer self-assembly; the resulting cotton showed excellent flame retardant properties, superhydrophobicity and self-healing properties [ 24 ]. Our research group also achieved a good flame retardant effect on the cotton fabrics through the introduction of both APP and BPEI [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TiO 2 nanoparticles can be potentially harmful to the human body if they are directly touched or inhaled in the process of longterm use. Recently, Huang et al 37 demonstrated how the preparation of superhydrophobic cotton fabric with a double-coated construction was achieved by a simple multi-step dipping process. Multiple impregnations of the same hydrophobic component liquid were conducive to the further enhancement of superhydrophobicity and the improvement of the coating uniformity to a certain extent.…”
Section: Dip Coatingmentioning
confidence: 99%
“…The water contact angle (WCA) of a superhydrophobic surface is greater than 150 °, and the slide angle (SA) is less than 10°. Superhydrophobic performance may be attained by building appropriate hierarchical micro/nanoscale structures to improve surface roughness, as well as modifying low-surface energy coatings [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%